Diagnostic accuracy of the rapid urine lipoarabinomannan test for pulmonary tuberculosis among HIV-infected adults in Ghana–findings from the DETECT HIV-TB study. Issue 1 (December 2015) - Bjerrum, Stephanie; Kenu, Ernest; Lartey, Margaret; Newman, Mercy; Addo, Kennedy; Andersen, Aase; Johansen, Isik
Abstract Background Rapid diagnostic tests are urgently needed to mitigate HIV-associated tuberculosis (TB) mortality. We evaluated diagnostic accuracy of the rapid urine lipoarabinomannan (LAM) test for pulmonary TB and assessed the effect of a two-sample strategy. Methods HIV-infected adults eligible for antiretroviral therapy were prospectively enrolled from Korle-Bu Teaching Hospital in Ghana and followed for minimum 6 months. We applied the LAM test on urine collected as a spot and early morning sample. Diagnostic accuracy was analysed for a microbiological TB reference standard based on sputum culture and Gene Xpert MTB/RIF results and for a composite reference standard including clinical follow-up data. Performance of sputum smear microscopy was included for comparison. Results Of 469 patients investigated for TB, the LAM test correctly identified 24/55 (44 %) of microbiologically confirmed TB cases. Sensitivity of the LAM test was positively associated with hospitalisation (67 %), Modified Early Warning Score > 4 (57 %) and subsequent death (71 %). LAM test specificity was 95 % increasing to 98 % for the composite reference standard. A two-sample LAM test strategy did not improve test performance. Using concentrated sputum for Ziehl-Neelsen and fluorescence microscopy in combination yielded a sensitivity of 31/55 (56 %) that increased to 35/55 (64 %) when the LAM test was added. Surprisingly, nontuberculous mycobacteria were cultured in 34/469 (7 %) and associated with a positive LAM test (p  = 0.008). Conclusions LAM test sensitivity was highest in patients with poor prognosis and subsequent death and did not increase with a two-sample strategy. A rigorous sputum microscopy strategy had superior sensitivity, but the simplicity of the LAM test holds operational possibilities as a TB screening method among severely sick patients.